Estimation of the Separation of Two Matrices (Journal of Computational Mathematics, 1984)
The estimation of the solution to the matrix equation AX-XB=C is primarily dependent on the quantity sep(A,B) introduced by Stewart. Varah has given some examples to show that $sep_F(A,B)$ can be very small even though the eigenvalues of A and B are well separated. In this paper we give some lower bounds of $sep_F(A,B)$.